Perundungan dalam Geguritan Cupak Gerantang - Baskara, I Gusti Agung Bagus Cakra; Putra, Ida Bagus Rai; Puspawati, Luh Putu (Humanis; Vol 26 No 3 (2022)DO - 10.24843/JH.2022.v26.i03.p08, 2022)
Gerantang". The results of this study describe the bullying found in traditional Balinese literary works, namely Geguritan Cupak Gerantang. The use of literary sociology theory in this analysis is able to reveal aspects of bullying which is one of the social phenomena in society contained in geguritan. The methods and techniques used consist of three steps, namely: (1) Providing data using the listening method accompanied by note-taking techniques and translation techniques, (2) The data analysis using qualitative methods and supported by analytical descriptive techniques, (3) presentation of the results of data analysis using informal methods accompanied by inductive and deductive techniques. The bullying aspect found in Geguritan Cupak Gerantang is shown by the interactions between the characters, which include the types of bullying, the factors behind the bullying, and the impact of the bullying.